2011
DOI: 10.1111/j.1708-8208.2011.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Clinical, Microbiological, and Radiographic Outcomes of Brånemark™ Implants Installed in Augmented Maxillary Bone for Fixed Full‐Arch Rehabilitation

Abstract: Purpose:To document the long-term outcome of Brånemark implants installed in augmented maxillary bone and to identify parameters which are associated with peri-implant bone level. Material and methods: Patients of a periodontal practice who had been referred to a maxillofacial surgeon for iliac crest bone grafting in the atrophic maxilla were retrospectively recruited. Five months following grafting they received 7 to 8 turned Brånemark implants. Following submerged healing of another 5 months, implants were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
(56 reference statements)
0
17
1
Order By: Relevance
“…Several differences have been found with this methodology. As expected, plaque and bleeding on probing scores have been significantly correlated with sulcular levels of bacteria [58], although the total DNA count was not significantly different between implants with shallow and deep pockets [59]. However, other studies involving a greater number of patients also found total DNA count to be correlated to interproximal bleeding index (r = 0.409) and interproximal probing depth (r = 0.307) but no correlations were present with plaque index or radiographic bone level up to 22 years after implant placement [60].…”
Section: Resultsmentioning
confidence: 78%
“…Several differences have been found with this methodology. As expected, plaque and bleeding on probing scores have been significantly correlated with sulcular levels of bacteria [58], although the total DNA count was not significantly different between implants with shallow and deep pockets [59]. However, other studies involving a greater number of patients also found total DNA count to be correlated to interproximal bleeding index (r = 0.409) and interproximal probing depth (r = 0.307) but no correlations were present with plaque index or radiographic bone level up to 22 years after implant placement [60].…”
Section: Resultsmentioning
confidence: 78%
“…The residual bone volume below the maxillary sinus is more determining for the implant's survival and success than the bone graft . Also autologous bone demonstrates an unpredictable resorption pattern . Another approach is the use of onlay bone grafts, which are often harvested from the hip or the calvarian bone.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies [30] [33] to duplicate the angle of occlusion. However, reconstruction varies among cases due individual differences.…”
Section: Discussionmentioning
confidence: 99%